Comparative Transcriptome Analysis Provides Insights Into the Mechanism by Which 2,4-Dichlorophenoxyacetic Acid Improves Thermotolerance in Lentinula edodes - Xu, Ruiping; Zhou, Shasha; Song, Jiaxin; Zhong, Haiying; Zhu, Tianwen; Gong, Yuhua; Zhou, Yan; Bian, Yinbing (Frontiers in Microbiology, 2022)
As the widest cultivated edible mushroom worldwide, Lentinula edodes suffers serious yield and quality losses from heat stress during growth and development, and in our previous study, exogenous 2,4-Dichlorophenoxyacetic acid (2,4-D) was found to improve the thermotolerance of L. edodes strain YS3357, but the molecular mechanism remains unclear. Here, we explored the potential protective mechanism of exogenous 2,4-D against heat stress by transcriptome analysis. 2,4-D possible improve the thermotolerance of L. edodes through regulating antioxidant genes, transcription factors, energy-provision system, membrane fluidity, and cell wall remodeling. Furthermore, 2,4-D was also found to regulate the saturation levels of fatty acids and ATP content in L. edodes mycelium under heat stress. This study proposed a regulatory network of 2,4-D in regulating L. edodes response to heat stress, providing a theoretical basis for improving L. edodes thermotolerance, and facilitating the understanding of the molecular mechanism of exogenous hormones in alleviating abiotic stress damage to macrofungi.